The pharmacological properties of ayahuasca - Escobar Cornejo, Guillermo Saúl (2015)
It describes the chemical characteristics and the effects of Ayahuasca consumption, in order to know the current status of the discoveries to date regarding their pharmacological properties. A literature review was performed on studies of ayahuasca until 2013 in English, Spanish, and Portuguese in the databases of PubMed, PsycINFO, Psyke, Psicodoc, and Redalyc; as well as chapters in books and literature obtained from related research. It is concluded that one of the components of ayahuasca – harmina – can be used to treat different pathologies.